Fetomaternal Outcome in Preterm Premature Rupture of Membranes: A Retrospective Study - Shree.J, Raveena; Sailatha.R, Sailatha.R (Journal of Neonatal Surgery, 2025)
Background: Preterm Premature Rupture of Membranes (PPROM) is a significant obstetric complication that occurs when the fetal membranes rupture before 37 weeks of gestation, often leading to preterm birth and associated neonatal morbidities. PPROM is linked to an increased risk of maternal infections, neonatal respiratory distress syndrome (RDS), sepsis, and other complications. Despite advancements in perinatal care, managing PPROM remains challenging due to its unpredictable nature and the risks associated with both expectant and active management strategies. Methods: A retrospective, non-comparative observational study was conducted at Chettinad Hospital and Research Institute over a 24-month period (January 2022 – December 2024). A total of 82 pregnant women diagnosed with PPROM between 24 and 36 weeks of gestation were included. Data were collected from electronic medical records, including maternal demographics, mode of delivery, neonatal birth weight, APGAR scores, NICU admissions, and maternal complications. Statistical analysis was performed using Chi-square and t-tests, with p<0.05 considered statistically significant. Results: The mean maternal age was 28 years (±4 years), and the mean gestational age at PPROM was 32 weeks (±2 weeks). 60% of deliveries were vaginal, while 40% required a C-section, primarily due to fetal distress (50%). 50% of neonates required NICU admission, with RDS (25%) and neonatal sepsis (10%) being the most common complications. Maternal complications were observed in 20% of cases, with chorioamnionitis (15%) being the most frequent. Conclusion: PPROM significantly increases the risk of preterm birth, neonatal morbidity, and maternal infections. Early diagnosis, timely interventions, and individualized management strategies are essential for optimizing outcomes. Future research should focus on improving risk prediction models and refining management protocols to reduce neonatal and maternal complications associated with PPROM.